Chlorhexidine Wound Lavage and Suture Soaking for Prevention of Suture-Related Infections - Wendelburg, K.; Smeak, D. D.; Kowalski, J.J. (Veterinary and Comparative Orthopaedics and Traumatology, 1988)
The effectiveness of chlorhexidine in preventing suture-related infections in two groups of dogs at high and low levels of bacterial contamination was examined. Prior to placing the sutures, the lateral stifle incisions were inoculated with Staphylococcus aureus and lavaged with either a 1 % chlorhexidine solution (treated groups) or sterile normal saline (control groups). Chlorhexidine significantly reduced the initial bacterial numbers and clinical inflammatory response in wounds contaminated with high or low numbers of bacteria. Chlorhexidine significantly decreased the tissue inflammation associated with the polyester sutures when contaminated with high concentrations of bacteria.
Keywords: Chlorhexidine; Suture-related infection; Surgical wound infection; Wound lavage